PERAN KEPALA SEKOLAH DALAM KEBIJAKAN DAN IMPLEMENTASI KURIKULUM MERDEKA (STUDI KASUS PADA MATA PELAJARAN PPKN UNTUK MENDUKUNG PENCAPAIAN HASIL BELAJAR SISWA DI SMA MUHAMMDIYAH 2 PALEMBANG) - Dian Maulina; Meta Melyani; Putri Pauziah (STKIP Subang, 2026)
The implementation of the Independent Curriculum requires effective school leadership support and the role of teachers who are able to create student-centered learning. This study aims to analyze the role of the principal in the policy and implementation of the Independent Curriculum in the Pancasila and Citizenship Education (PPKn) subject to support student learning outcomes at SMA Muhammadiyah 2 Palembang. This research employed a qualitative method, focusing on a case study approach. Data was gathered using observation, interviews, and written records. The people who provided information for the research were the school principal and the PPKn teachers, as they were directly involved in carrying out the Independent Curriculum. The results showed that the principal plays a role as a director, supervisor, evaluator, and policymaker in the implementation of the education program. Curriculum policies are formulated based on educational report cards, then developed through the preparation of school work plans involving the vice principal and teachers. The implementation of the Independent Curriculum is carried out through socialization activities, workshops, supervision, evaluation, training, and technical guidance in the form of Workshops on Learning Digitalization, School-Based Management, and Academic Information Systems. In Civics (PPKn), teachers act as facilitators by implementing discussion methods, case studies, and project-based learning. Student learning outcomes demonstrate good achievement, with average scores above the Minimum Completion Criteria. This study concludes that the principal's collaborative and participatory leadership supports the successful implementation of the Independent Curriculum and contributes to improved student learning outcomes in Civics (PPKn).